Organizing the space of Tuong Binh Hiep lacquer craft village, Thu Dau Mot city, Binh Duong province - Cu, Thị Ánh Tuyết; Le, Tống Thanh Tuyền; Nguyen, Văn Dũng (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Lacquer not only has artistic value but also has historical value for the Vietnamese people. For a long time, Thu Dau Mot city in Binh Duong province has been considered an important trading port of the southern region, where lacquer paintings are bought, sold and transported not only domestically but also abroad. The topic focuses on learning about the concepts as well as the historical development process of traditional craft villages, especially Tuong Binh Hiep lacquer craft. Through research methods to learn about the current status as well as spatial organization models of craft village areas in Tuong Binh Hiep ward, Binh Duong province, the research team proposed a solution to partition the research area into areas with specific functions but not separate from the overall image of a traditional lacquer craft village, contributing to the development of craft village tourism.